THE RELATIONSHIP AMONG COMMUNITY SPIRIT, COMMUNITY IDENTIFICATION, AND COMMUNITY LOYALTY OF ONLINE SPORTS COMMUNITY USER - Jae-Keun Yang (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
The purpose of the study is to examine the relationship among community spirit, community identification, and community loyalty of online sports community user. To accomplish the purpose of the study, adult users of "N" research engine are subjected to questionnaire. Based on convenience sampling, 383 questionnaires are used for final data analysis. By utilizing SPSS 21.0, frequency analysis, exploratory factor analysis, reliability analysis, simple regression analysis and multiple regression analysis are implemented and the results are as follows. First, community spirit of online sports community user influences on community identification. Second, community spirit of online sports community user influences on community loyalty. Third, community identification of online sports community user influences on community loyalty.